Disaster risk management in business education entrepreneurial formation for corporate sustainability - Carolina Herrera-Cano (AD-minister, 2016)
The purpose of this paper is to show the importance of business education in Disaster Risk Manage-ment (DRM). This paper aims to evaluate the awareness level of the Master in Business Administra-tion’s (MBA) students regarding the importance disaster risk management (DRM) plays. This paper develops a literature review concerning the concept of disasters, Disaster Risk Management, Disaster Risk Reduction, and the role of MBA programs. Furthermore, a survey at Universidad EAFIT (Medellin, Colombia) was designed and implemented as primary source information with the purpose of showing the DRM awareness level of MBA’s students. Finally, a case study connecting DRM with entrepre-neurship formation is described. This paper identified a limited formal education in DRM Latin Ameri-can MBA programs, and specifically at Universidad EAFIT. Additionally, a lack of awareness in MBA’s students about the importance of DRM was identified. In this sense, the paper proposes a DRM edu-cation model that uses a Corporate Social Responsibility (CSR) and entrepreneurial formation in busi-ness education. This study aims to show the importance of the inclusion of disaster risk reduction and management knowledge as part of the courses in: Corporate Social Responsibility (CSR), Sustainabili-ty, and Entrepreneurship content in Masters in Business Administration (MBA) programs.